Marginalidad y ética de la marginalidad en la nueva ciudad narrada por la novela negra latinoamericana - Valle, Amir (Anales de Literatura Hispanoamericana, 2008)
In recent Latin American narrative, detective novels are becoming increasingly prominent, and display a novelty due basically to their rereading and rediscovering of new social limits in the Latin American countries in which they are produced. Latin America neo-detective narrative, according to a group of critics in this field, has endowed the continent’s intellectual and social debate with a new kind of city: a city that is submerged and marginalised, not voluntarily, but as a consequence of greater forces, as fate; a city which shares the same temporal framework as that other city, far more frequently novelised, which speaks of high society and of the major problems of the high classes in a more panoramic and historical manner. This city is a ctiy of losers. A city which, with small variations according to the historical and socioeconomic conditions of each particular country, writers are discovering (and reliving) in their novels, thus mirroring the fast-moving process of marginalisation in contemporary Latin America society.